2023
DOI: 10.1177/00037028231180233
|View full text |Cite
|
Sign up to set email alerts
|

Linearly Polarized Infrared Spectroscopy for the Analysis of Biological Materials

Abstract: The analysis of biological samples with polarized infrared spectroscopy (p-IR) has long been a widely practiced method for the determination of sample orientation and structural properties. In contrast to earlier works, which employed this method to investigate the fundamental chemistry of biological systems, recent interests are moving toward “real-world” applications for the evaluation and diagnosis of pathological states. This focal point review provides an up-to-date synopsis of the knowledge of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 222 publications
0
3
0
Order By: Relevance
“…The same area of the sample was analyzed at eight different rotations of the polarizers for each configuration (0–157.5, and 22.5° increments). For the single polarizer measurement, the choice to insert the polarizer into the analyzer position was made to avoid any spatial shifts of the analyzed region of the sample, which may have been induced by the insertion and removal of the analyzer, thus enabling a direct comparison of the same region of the sample in the single polarizer and polarizer–analyzer setups. , Subsequently, the multiple polarization angle method was applied to the analyzer-only data set, and pixels that exhibited R 2 values greater than 0.997 and an azimuth angle between 85 and 90° were extracted, and the spectra averaged per polarizer angle (1268 spectra per angle). Pixels corresponding to the same coordinates as those extracted from the analyzer-only data set were also extracted from the polarizer–analyzer data set and averaged per polarizer angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same area of the sample was analyzed at eight different rotations of the polarizers for each configuration (0–157.5, and 22.5° increments). For the single polarizer measurement, the choice to insert the polarizer into the analyzer position was made to avoid any spatial shifts of the analyzed region of the sample, which may have been induced by the insertion and removal of the analyzer, thus enabling a direct comparison of the same region of the sample in the single polarizer and polarizer–analyzer setups. , Subsequently, the multiple polarization angle method was applied to the analyzer-only data set, and pixels that exhibited R 2 values greater than 0.997 and an azimuth angle between 85 and 90° were extracted, and the spectra averaged per polarizer angle (1268 spectra per angle). Pixels corresponding to the same coordinates as those extracted from the analyzer-only data set were also extracted from the polarizer–analyzer data set and averaged per polarizer angle.…”
Section: Resultsmentioning
confidence: 99%
“…Polarized Fourier transform infrared spectroscopy (p-FTIR) is a popular technique for determining orientational information of organic samples. This technique is a longstanding practice applied to a broad range of samples, including bulk polymers, fibers, and biological materials. The ability to characterize orientational information in these samples by p-FTIR is dependent on linear dichroism, where absorption is proportional to the alignment of the electric field vector of the incident light and the preferential orientation of the vibrational modes’ transition dipole moment. Typically, measurements of bulk samples are performed by inserting a polarizer in the path of the incoming beam inside an infrared (IR) spectrometer and collecting two sets of spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of absorption-dominated transmission changes, it is shown that a cos-fit can be used for each pixel of the camera and obtained using only three points (three from four polarisation images). This technique is demonstrated for transmission and reflection modes using natural olivine micro-crystals, but it is fully transferable to other polarisationresolved imaging techniques; e.g., bio-medical techniques [14,15], 3D optical coherent tomography [16,17], analysis of structural colours in natural materials [18], and industrial applications, such as edge detection of fast moving materials and workpieces [19].…”
Section: Introductionmentioning
confidence: 99%